Seasonal to decadal variations of sea surface pCO2 and sea‐air CO2 flux in the equatorial oceans over 1984–2013: A basin‐scale comparison of the Pacific and Atlantic Oceans. Issue 5 (18th May 2015) - Wang, Xiujun; Murtugudde, Raghu; Hackert, Eric; Wang, Jing; Beauchamp, Jim
Abstract The equatorial Pacific and Atlantic Oceans release significant amount of CO2 each year. Not much attention has been paid to evaluating the similarities and differences between these two basins in terms of temporal variability. Here we employ a basin‐scale, fully coupled physical‐biogeochemical model to study the spatial and temporal variations in sea surface pCO2 and air‐sea CO2 flux over the period of 1984–2013 in the equatorial Pacific and Atlantic Oceans. The model reproduces the overall spatial and temporal variations in the carbon fields for both basins, including higher values to the south of the equator than to the north, the annual maximum sea surface pCO2 in boreal spring, and the annual peak in sea‐to‐air CO2 flux in boreal fall in the upwelling regions. The equatorial Pacific reveals a large interannual variability in sea surface pCO2, which is associated with the El Niño–Southern Oscillation. As a contrast, there is a strong seasonality but little interannual variability in the carbon fields of the equatorial Atlantic. The former is driven by the variability of dissolved inorganic carbon but the latter by sea surface temperature. Our model estimates an average sea‐to‐air CO2 flux of 0.521 ± 0.204 Pg C yr−1 for the tropical Pacific (18°S–18°N, 150°E–90°W), which is in good agreement with the observation‐based estimate (0.51 ± 0.24 Pg C yr−1). On average, sea‐to‐air CO2 flux is 0.214 ± 0.03 Pg C yr−1 in the tropical Atlantic (10°S–10°N), which compares favorably with observational estimates.